Pengarusutamaan Moderasi Islam di Masjid Nasional al-Akbar Surabaya (MAS) - Muktafi, Muktafi (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2018)
This article discusses the dynamics of mainstreaming Moderate Islam in the Masjid Nasional Al-Akbar Surabaya (MAS) by analyzing how the design of Islamic moderation developed by MAS managers. This article also analyzes the sermon material delivered by the preachers during a khutbah on Friday can have an impact on mainstreaming moderate Islam. The construction of Moderate Islam at the MAS is Islam raá¸¥mah li al-â€˜ÄlamÄ«n by carrying out and upholding five basic principles, namely: tawÄsuá¹, tawÄzun, taâ€˜Ädul, tasÄmuá¸¥, and amr maâ€˜rÅ«f wa nahy â€˜an al-munkar bi al-maâ€˜rÅ«f. The dynamics of mainstreaming Moderate Islam carried out by MAS is with the strategy of escorting daâ€˜wah starting from choosing khotib/dai, determining the themes of Islam that give mercy to all humans by upholding al-akhlÄq al-karÄ«mah according to MASâ€™s vision, mission and value by putting forward mandate, istikamah, giving uswah, being responsible, and li jamÄ«â€˜ al-ummah).